Maskulinitas dalam Film Indonesia (Analisis Isi Kuantitatif Maskulinitas pada Film Aksi Indonesia Produksi 2011-2021) - Olivia Andita Oktaviana; Monika Pretty Aprilia (Universitas Majalengka, 2022)
Action films are closely related to dangerous physical scenes. In those action films it shows much that the person or character is a man, because the man is often considered a strong, muscular, strapping person who is very fit for an action movie. A man having such characteristics is usually called a masculine male. Following are some of Indonesia's action films showing scenes of masculinity, the Hit&Run (2019), Gundala (2019), 22 Minutes (2018), Partikelir (2018), Headshot (2016) and The Raid: Redemption (2011). Researchers analyzing the masculinity of the six films using seven concepts of masculinity presented by Janet Salfetz, by masculinity can be seen from physical appearance, functional, sexuality, emotional, intellectual, interpersonal and personal character. This study has made ita goal to identify the frequency of masculinity in our action films and to learn the form of masculinity in action films. This type of research is a descriptive study using a quantitative analysis of content. The six films above as objects of his research. Results in this study revealed that the true form of masculinity was 29%, the sexuality of 26% men, the interpersonal 14%, the personal character of men 10%, the intellectual men 9%, functional men 8%,